2019
DOI: 10.1080/14737159.2020.1690456
|View full text |Cite
|
Sign up to set email alerts
|

How does carrier status for recessive disorders influence reproductive decisions? A systematic review of the literature

Abstract: Introduction: Carrier screening for recessive disorders is undertaken by prospective parents to inform their reproductive decisions. With the growing availability of affordable and comprehensive expanded carrier screening (ECS), it is expected that carrier screening will become a standard practice in the future. However, the impact of positive carrier screening results on the reproductive decisions of at-risk couples (ARCs) remains underexplored. Areas covered:We performed a systematic literature review to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Measuring informed choice has, however, proven difficult, especially since there seems to be no consensus on the best methodology for the evaluation of informed decision-making. To shed more light on how screening results impact the reproductive choices of carrier couples, studying longer-term outcomes can provide helpful insights (Cannon et al 2019 ), but similar to neonatal screening, it is not easy to follow these couples over time.…”
Section: Dynamics In Screening Criteria For Rare Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring informed choice has, however, proven difficult, especially since there seems to be no consensus on the best methodology for the evaluation of informed decision-making. To shed more light on how screening results impact the reproductive choices of carrier couples, studying longer-term outcomes can provide helpful insights (Cannon et al 2019 ), but similar to neonatal screening, it is not easy to follow these couples over time.…”
Section: Dynamics In Screening Criteria For Rare Diseasesmentioning
confidence: 99%
“…However, carrier screening does not replace NBS, nor does NBS diminish the potential benefit of carrier screening (ACOG 2017 ). NBS is still important, as often a screening test will not detect all carriers, and not all prospective parents will decide to participate (Stafler et al 2016 ) or act on their screening results (Cannon et al 2019 ).…”
Section: How Innovations Make Debates Convergementioning
confidence: 99%
“…Those reviews that address data analysis and risk of bias in their methods, identi ed issues with outcome heterogeneity, study design, and overall quality of evidence, whilst others that didn't speci cally address these issues performed narrative syntheses, which is indicative that a meta-analysis was not possible with the available data. (23,(25)(26)(27)(28) We propose developing a core outcome set (COS) for RGCS. A COS is an agreed minimum set of outcomes that should be measured and reported in all studies on a particular topic.…”
Section: Rgcsmentioning
confidence: 99%
“…Earlier studies demonstrated that carrier screening for (mainly) single, or a few conditions is not associated with major adverse psychological reactions and initial feelings of psychological distress mostly dissipate over time (64). A recently published review on reproductive decisions for those identified as carrier couples demonstrates that most couples decide to change their reproductive plans to avoid conceiving a child with a severe genetic condition (150).…”
Section: Balancing Harms and Benefitsmentioning
confidence: 99%
“…However, one should be aware that this may lead to false reassurance if couples do not understand the residual risk or that ECS does not guarantee future children will not have genetic conditions (38). A recently published review on reproductive decisions for those identified as carrier couples demonstrates that most couples decide to change their reproductive plans to avoid conceiving a child with a severe genetic condition (150). Due to the (expected) absence of test-positive results, I could not investigate this nor was that my aim.…”
Section: Reproductive Intentionsmentioning
confidence: 99%